Contracting and Accountability Under Leaner Government. (14th November 2017) - Berrios, Ruben; McKinney, Jerome B.
Abstract : Federal government contracting has increased over the past three decades as a way to reduce costs and to promote greater efficiency and effectiveness in the procurement system. In making contracting decisions and calculating cost savings, however, officials do not always take into account all costs associated with the process. Transaction cost theory is used to analyze the costs incurred in contracting for gathering information, negotiation, and enforcement. Additionally, ethinomics is used to show that contracting can create circumstances that leave agencies open to unethical behavior with both monetary and social consequences. Despite documented improvement in resource allocation since 2009, many agencies still do not provide enough funding and adequate personnel to capture and reduce transaction costs in contract evaluation, monitoring, and performance outcome.